The Danish labor market, 2000-2018 - Torben M. Andersen (IZA World of Labor, 2019)
Denmark is often highlighted as a “flexicurity” country characterized by lax employment protection legislation, generous unemployment insurance, and active labor market policies. Despite a sharp and prolonged decline in employment in the wake of the Great Recession, high job turnover and wage adjustments worked to prevent increased long-term and structural unemployment. Most unemployment spells were short, muting the effects on long-term and youth unemployment. Recent reforms boosted labor supply and employment, targeting the young, elderly, and immigrants. Employment recovered to its structural level around 2015 and has since increased due to a favorable business cycle situation and structural reforms (particularly increases in retirement age).
Keywords: F44; L1; J1; J6; J61; 330; flexicurity; business cycles; structural policies; youth unemployment; immigration